Solar Radio Burst Statistics and Implications for Space Weather Effects - Giersch, O.; Kennewell, J.; Lynch, Mervyn (2017)
Solar radio bursts have the potential to affect space and terrestrial navigation, communication, and other technical systems that are sometimes overlooked. However, over the last decade a series of extreme L band solar radio bursts in December 2006 have renewed interest in these effects. In this paper we point out significant deficiencies in the solar radio data archives of the National Centers for Environmental Information (NCEI) that are used by most researchers in analyzing and producing statistics on solar radio burst phenomena. In particular, we examine the records submitted by the United States Air Force (USAF) Radio Solar Telescope Network (RSTN) and its predecessors from the period 1966 to 2010. Besides identifying substantial missing burst records we show that different observatories can have statistically different burst distributions, particularly at 245 MHz. We also point out that different solar cycles may show statistically different distributions and that it is a mistake to assume that the Sun shows similar behavior in different sunspot cycles. Large solar radio bursts are not confined to the period around sunspot maximum, and prediction of such events that utilize historical data will invariably be an underestimate due to archive data deficiencies. It is important that researchers and forecasters use historical occurrence frequency with caution in attempting to predict future cycles.